The geometry of the Iapetus Suture Zone in central Ireland deduced from a magnetotelluric study - Rao, C.K.; Jones, Alan G.; Moorkamp, Max (My University, 2007)
The crustal geometry of the Iapetus Suture Zone (ISZ) in central Ireland is inferred from an electrical resistivity model derived from broadband and long period magnetotelluric measurements along a 200-km-long NNW-SSE profile. The model highlights an undulating high conductivity layer of thickness 10–15 km and resistivity 2–5 Ω m, at middle to lower crustal depths interpreted as sulphide-bearing graphitic sediments deposited between the converging continents of Laurentia and Avalonia during the closure of the Iapetus Ocean. The sediments underwent sinistral, transpressional deformation during convergence, and movements along the faults transported the sediments to depths of 5–10 km forming the U-shaped conductor beneath the centre of the profile correlative with the inferred location of the Iapetus Suture Zone. Two high resistivity blocks identified above the U-shaped conductor are interpreted as Caledonian granite bodies, and likely relate to late Caledonian igneous activity.
Keywords: Magnetotellurics; Iapetus suture; Ireland; Tectonics; Geometry; Iapetus Suture Zone; ISZ